Application of Lesson Study in Guidance and Counseling Services - Wibowo, Satrio Budi; Susanto, Eko (Universitas Muhammadiyah Metro, 2020)
Lesson Study (LS) has been widely practiced by class teachers to improve the quality of learning in class. Lesson Study, which consists of the planning process (plan), the practice of carrying out learning (do), and reflection for improvement (see), is used by the classroom teacher to improve the process and learning outcomes. LS is applied to settings classical class. Information and orientation services in Guidance & Counseling (BK), almost similar to implementation Classroom learning, is given in a classical format. Information services are efforts that are made to meet students' lack of information, which can be done with several techniques such as conventional lectures, as well as with courses interactive with the help of media usage. Neither the orientation services are services provided in a classical format in a class aimed at helping students order able to adjust to the environment or new situations. So if Observing the application of LS can also be done on BK services, especially on services information and orientation. This paper discusses how to apply LS in BK service. The application of LS is expected to improve the quality of services provided by the BK teacher in the class.